2020
DOI: 10.1016/j.ijid.2020.03.076
|View full text |Cite
|
Sign up to set email alerts
|

Spatial epidemic dynamics of the COVID-19 outbreak in China

Abstract: Background: On 31 December 2019 an outbreak of COVID-19 in Wuhan, China, was reported. The outbreak spread rapidly to other Chinese cities and multiple countries. This study described the spatio-temporal pattern and measured the spatial association of the early stages of the COVID-19 epidemic in mainland China from 16 January-06 February 2020. Methods: This study explored the spatial epidemic dynamics of COVID-19 in mainland China. Moran's I spatial statistic with various definitions of neighbours was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
311
1
26

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(344 citation statements)
references
References 7 publications
6
311
1
26
Order By: Relevance
“…However, mapping of disease incidence to identify spatial clustering and patterns remains an important pathway to understanding disease epidemiology and is required for effective planning, prevention or containment action [11][12][13]. There are a few studies that attempt to map the pandemic in China [14] and in Iran [15]. However, the temporal dynamic of the COVID-19 pandemic has not been taken into account in order to assess space-time dynamics although a descriptive representation of the spatio-temporal pattern of the CFR was published for Brazil [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, mapping of disease incidence to identify spatial clustering and patterns remains an important pathway to understanding disease epidemiology and is required for effective planning, prevention or containment action [11][12][13]. There are a few studies that attempt to map the pandemic in China [14] and in Iran [15]. However, the temporal dynamic of the COVID-19 pandemic has not been taken into account in order to assess space-time dynamics although a descriptive representation of the spatio-temporal pattern of the CFR was published for Brazil [16].…”
Section: Introductionmentioning
confidence: 99%
“…Following the disease's dynamics and the exponential growth of the number of cases, several studies have been reported [2][3][4][5]. Particularly, those that perform temporal and spatial analyses of COVID-19 have demonstrated the impact of morbidity, mortality and global geographical dissemination of the disease in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, those that perform temporal and spatial analyses of COVID-19 have demonstrated the impact of morbidity, mortality and global geographical dissemination of the disease in the world. The use of aggregate spatial data allows to map the patterns of the rapid progression of the disease and to support decision-making in the allocation of resources for the prevention and control of COVID-19 in priority areas [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…An OD flow graph is a visual analysis method that connects the starting place and destination with straight lines or curves, reflecting the OD flow through line thickness [25][26][27][28][29][30]. In this paper, the location information of the source and destination of the migration provided by the Baidu migration data is used to conduct clustering processing according to the time information of the migration data.…”
Section: Model Of Epidemic Transmission Forcementioning
confidence: 99%